2017
DOI: 10.18632/oncotarget.19478
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes and pathways in nasopharyngeal carcinoma by bioinformatics analysis

Abstract: Nasopharyngeal carcinoma is a metastatic malignant tumor originating from nasopharyngeal epithelium. Lacking or nonspecific symptoms of patients with early stage nasopharyngeal carcinoma have significantly reduced the accuracy of diagnosing and predicting nasopharyngeal carcinoma development. This study aimed to identify gene signatures of nasopharyngeal carcinoma and uncover potential mechanisms. Two gene expression profiles (GSE12452 and GSE13597) containing 56 nasopharyngeal carcinoma samples and 13 normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 58 publications
2
20
0
Order By: Relevance
“…Cdk1, Ccnb1, Plk1, Top2a, and Ccna2 were determined and confirmed as hub–bottleneck nodes that serve significant roles in cell cycle function. These central genes are in accordance with previous findings from PPI network analysis (Chen et al, ; Chen et al, ). Besides, five modules were selected in the PPI network, genes of which were mainly downregulated in these modules and enriched in cell cycle and DNA replication process.…”
Section: Discussionsupporting
confidence: 92%
“…Cdk1, Ccnb1, Plk1, Top2a, and Ccna2 were determined and confirmed as hub–bottleneck nodes that serve significant roles in cell cycle function. These central genes are in accordance with previous findings from PPI network analysis (Chen et al, ; Chen et al, ). Besides, five modules were selected in the PPI network, genes of which were mainly downregulated in these modules and enriched in cell cycle and DNA replication process.…”
Section: Discussionsupporting
confidence: 92%
“…revealed that GSE12452 from the GEO database included 31 NPC samples and 10 normal samples and highlighted MAD2L1, CCNB1, PCNA, ALDH1A1, and MUC1 as the genes that were correlated with NPC. In addition, the DEGs retrieved from the expression data sets (GSE12452 and GSE13597) and hub genes identified from PPI were reported to highly participate in biological processes of NPC and these molecular factors could improve the understanding of the underlying mechanism of NPC, thus providing novel insights into the diagnosis and treatment of NPC . Similarly, Jiang et al .…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the DEGs retrieved from the expression data sets (GSE12452 and GSE13597) and hub genes identified from PPI were reported to highly participate in biological processes of NPC and these molecular factors could improve the understanding of the underlying mechanism of NPC, thus providing novel insights into the diagnosis and treatment of NPC. 37 Similarly, Jiang et al 38 used the expression data set GSE12452 to investigate the underlying mechanism of NPC and highlighted the DEGs (PTGS2, FN1, CXCL9, CXCL10, ZIC2, and OVOL1) as potential therapeutic targets for NPC. Figure 4 The intersection of nasopharyngeal carcinoma-related DEGs and genes from the blue module.…”
Section: Discussionmentioning
confidence: 99%
“…Integration and analysis of gene chip data to obtain more consistent results has become problematic. Some researchers choose to do meta-analysis of multiple gene expression profiles based on different platforms or from a number of types of cells, whereas others chose to integrate data based on the same platform (25)(26)(27). Additional molecular biology experiments may be needed to conclude which method provides more accurate results.…”
Section: Discussionmentioning
confidence: 99%